(untitled) (Global Journal of Human-Social Science, 2012)
The current study analyze the social structural dimension of Pakhtun society emphasizing on the cultural economic physical religious and political factors to women s education A quantitative approach was adopted and the data was collected from 323 male and female respondents of eight Union Councils of District Dir lower using stratified random sampling proportionate method and interview schedule The data was analyzed using SPSS and discussion was made over the collected data The empirical results show that there exists a strong relationship between the structural impediments including system of patriarchy male dominance customs and traditions religious misinterpretation feudalism etc and women s education The analysis further suggested that a comprehensive strategy including provision of education the role of mass media policy making in regard to women s empowerment and religious knowledge and the role of religious leader is basic for brining equality at the educational spheres